2021
DOI: 10.1111/imj.14813
|View full text |Cite
|
Sign up to set email alerts
|

Association between 5‐hydroxytryptamine gene polymorphism rs140700 and primary insomnia in Chinese population

Abstract: Background: Primary insomnia is a worldwide problem and it has a considerable negative impact on one's physical and mental health. Studies have shown that nonsynonymous Single-nucleotide polymorphisms in 5-hydroxytryptamine (serotonin or 5-HT) are related to primary insomnia. Previous studies have shown that 5-HT polymorphism (rs140700) is related to depression, and insomnia is often accompanied by depression and anxiety. The relationship between this site and primary insomnia is unknown. We speculated that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…5-TH and β-EP are monoamine neurotransmitters, which are related to behavior and emotion, and participate in the regulation of sleep-wake cycle, so changes in their levels can truly reflect the quality of sleep. [21] In this study, the level of 5-TH and β-EP were obviously increased in study group after treatment. On the one hand, it can benefit from the regulating effect of Dan-shen in Ningshen mixture on neurotransmitters; On the other hand, it may be beneficial that acupuncture can regulate the activity and content of neurotransmitters by regulating the function of the neuroendocrine system.…”
Section: Discussionmentioning
confidence: 57%
“…5-TH and β-EP are monoamine neurotransmitters, which are related to behavior and emotion, and participate in the regulation of sleep-wake cycle, so changes in their levels can truly reflect the quality of sleep. [21] In this study, the level of 5-TH and β-EP were obviously increased in study group after treatment. On the one hand, it can benefit from the regulating effect of Dan-shen in Ningshen mixture on neurotransmitters; On the other hand, it may be beneficial that acupuncture can regulate the activity and content of neurotransmitters by regulating the function of the neuroendocrine system.…”
Section: Discussionmentioning
confidence: 57%
“…In this framework, the 5‐HTTLPR S‐allele was found to predispose to risk of stress‐related insomnia (Huang et al, 2021) and depression‐related insomnia (Polito et al, 2015), as well as insomnia (Deuschle et al, 2010; Huang et al, 2021; Pallesen et al, 2019), although other findings do not confirm an involvement of the 5‐HTTLPR allele or of other genes involved in the biosynthesis of 5‐HT in insomnia (Hui et al, 2021; Mei et al, 2018; van Dalfsen & Markus, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The examination of the substance composition across different parts revealed that the sour date fruit kernel (ZSS group) comprised the following compounds: (1) magnoflorine, (2) spinosin, (3) rutin, (4) 6 ′′′ -feruloylspinosin, (5) Jujuboside A1, (6) Jujuboside A, (7) Jujuboside B, (8) betulinic acid, (9) ceanothic acid, and (10) alphitolic acid. ZSF contained compounds (1), ( 2), (3), and (7-10), while ZSKS contained compounds (1) and (8)(9)(10). The common substance basis for the sedative and hypnotic effects of various parts of ZS may be the presence of compounds (1), ( 8), (9), and (10) across all parts of ZS.…”
Section: Saponinmentioning
confidence: 99%
“…5-HT, recognized as the “pleasure neurotransmitter”, exerts its functions within the brain through its extensive family of receptors. Notably, the 5-HT1 subfamily has emerged as a crucial target for therapeutic medications aimed at addressing psychiatric disorders [ 9 , 10 , 11 ]. GABA serves as a critical inhibitory neurotransmitter within the central nervous system (CNS), with the GABA A-type receptor (GABAAR) being mainly associated with insomnia symptoms [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%